Efektivitas Penggunaan Media Animasi Renderforest terhadap Hasil Belajar Pada Mata Pelajaran Pendidikan Pancasila Peserta Didik SMA Negeri 1 Indralaya - Amziyah, Dini; Chotimah, Umi (Universitas Muhammadiyah Ponorogo, 2026)
he Effectiveness of Using Renderforest Animation Media on Learning Outcomes in Pancasila Education Subjects for Students of SMA Negeri 1 Indralaya. This study aims to determine the effectiveness of the use of Renderforest animation media on the learning outcomes of students at SMA Negeri 1 Indralaya. This study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design. Data collection techniques are carried out through observation, tests and documentation. The research sample consisted of two classes, namely class X.6 as the experimental class and class X.3 as the control class. The number of samples in this study was 72 students. The data analysis techniques used included normality tests, homogeneity tests, and hypothesis tests with the help of SPSS version 27.00. The novelty of this research lies in the contextual use and testing of the effectiveness of Renderforest animation media in the subject of Pancasila Education at SMA Negeri 1 Indralaya. The results showed that student learning outcomes improved, with an average of 73.47 for the experimental class and 67.53 for the control class. The results of the independent sample t-test showed a significance level of .007, which is less than the significance level of .05, meaning that H0 was rejected and Ha was accepted. Thus, this shows that the use of Renderforest animation media is effective in improving student learning outcomes at SMA Negeri 1 Indralaya.